OPTIMALISASI TRAY AERATOR DAN FILTRASI PASIR LAMBAT (SPL) UNTUK MENURUNKAN KADAR BESI (FE) PADA AIR SUMUR GALI - Mualim; Adeko, Riang (JURNAL MEDIA KESEHATAN, 2024)
Water is a vital element that supports human life on earth. Water has various functions, such as for drinking, bathing, washing, and as a means of transportation in rivers and seas. Based on WHO (World Health Organization) data, the need for water in developed countries ranges from 60-120 liters per person per day, while in developing countries, including Indonesia, the need for water is only around 30-60 liters per person per day. This study aims to determine the effectiveness of the combination of Tray Aerator and filtration with slow sand filter media (SPL) in reducing iron (Fe) levels in dug well water in Padang Serai Village, Bengkulu City. This study used a quasi-experimental method with a pretest-posttest design (Sugiyono, 2015). The results showed that the decrease in iron (Fe) levels after using Tray Aerator reached 0.761 mg/l. Meanwhile, filtration with a slow sand filter was able to reduce iron levels by up to 0.672 mg/l. The combination of the two methods gave the best results with a decrease in iron levels of 0.872 mg/l, from an initial level of 1.022 mg/l. Of the three treatments, the combination of Tray Aerator and slow sand filter filtration proved to be the most effective in reducing iron (Fe) levels. To increase effectiveness, it is recommended to increase the thickness of the slow sand filter media and increase the number of trays on the Tray Aerator to maximize the process of reducing iron levels in dug well water.